Effect of Mixed Firing Ethylene Glycol on Combustion and Emission Performance of Model 4190 Diesel Engine. Issue 1 (1st January 2023) - Wang, Qiwei; Zhang, Feifei; Lin, Hang; Li, Pinfang; Fan, Jinyu; Ye, Zixiao; Huang, Jialiang
Abstract: In order to study the influence of ethylene glycol on the combustion and emission of marine diesel engine, a combustion chamber model was established based on 4190ZL C-2 marine medium speed diesel engine by AVL-FIRE simulation software, and the accuracy of the model was verified. The effects of ethylene glycol on the combustion and emission characteristics of diesel engine under different mixing ratios were studied by simulation experiments, and the optimal mixing ratio of ethylene glycol and diesel was obtained under the premise of ensuring the diesel engine to work at full load. The results show that the average pressure in the cylinder and the maximum burst pressure in the cylinder of the dual-fuel engine mixed with ethylene glycol are decreased compared with the original engine under different mixing ratios. Under full load condition, NOx and soot emissions are decreased by increasing ethylene glycol mixing ratio, and CO emission peak is increased but not significantly increased. Through analysis, it can be concluded that when mixing ratio is 15%, final CO emission decreases by 28.6%, final NO emission decreases by 7.9%, and Soot emission decreases by 16.9%.